Liberalizm i komunitarianizm: Analiza sporu - Chrobak, Karol (Kultura i Społeczeństwo, 2025)
This article addresses the dispute between the liberal and communitarian positions, analyzing differences in how the category of the “subject” is understood. Communitarians criticize their opponents primarily for their idealistic view of the subject—as a self-sufficient individual, independent of broader social contexts. In contrast, they argue that the subject should be understood as an individual rooted in a particular community, and only on this basis can they determine their own life project and define their individual interests. In this context, the category of the common good and its relation to the individual good becomes crucial for communitarians. The article’s conclusion identifies the divergence of perspectives behind the two positions as the source of the dispute: whereas liberalism focuses on questions of morality, communitarianism is primarily oriented toward the ontology of social reality.